Modified triaxial apparatus for shearing-infiltration test - Rahardjo, Harianto (2011)
A triaxial apparatus was modified and developed for performing shearing-infiltration tests under saturated and unsaturated conditions. Miniature pore-water pressure transducers were installed at different heights of the soil specimen for pore-water pressure measurement. Two different types of miniature pressure transducers were used, and problems associated with the transducers are discussed. Ancillary works and equipment to install the miniature transducers onto the soil specimen are also discussed. The measurement of air entry value of the small disk in the transducer was found to be very difficult. The results show that the soil specimen failed during infiltration due to increase in pore-water pressure or decrease in matric suction.